2010
DOI: 10.3354/ame01427
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic heterotrophic bacterial nutrition by semilabile DOM as revealed by data assimilative modeling

Abstract: Previous studies have focused on the role of labile dissolved organic matter (DOM) (defined as turnover time of ~1 d) in supporting heterotrophic bacterial production, but have mostly neglected semilabile DOM (defined as turnover time of ~100 to 1000 d) as a potential substrate for heterotrophic bacterial growth. To test the hypothesis that semilabile DOM supports substantial amounts of heterotrophic bacterial production in the open ocean, we constructed a 1-dimensional epipelagic ecosystem model and applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 38 publications
5
45
0
2
Order By: Relevance
“…Notably, this HMW fraction is made up primarily of carbohydrates (~50% in surface waters) with a fairly homogenous monosaccharide composition across major ocean basins indicating this material has a widespread and common source throughout the global ocean . Radiocarbon analysis of the monosaccharides making up HMW DOM carbohydrates indicates this fraction has an estimated residence time of <3 years consistent with the residence time of semi-labile DOM (100 to 1000 days) obtained from ecosystem models (Luo et al, 2010). Interestingly, the carbohydrate content of HMW DOM has been observed to decrease with depth indicating that polysaccharides are a major bio-reactive component McCarthy et al, 1993).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Notably, this HMW fraction is made up primarily of carbohydrates (~50% in surface waters) with a fairly homogenous monosaccharide composition across major ocean basins indicating this material has a widespread and common source throughout the global ocean . Radiocarbon analysis of the monosaccharides making up HMW DOM carbohydrates indicates this fraction has an estimated residence time of <3 years consistent with the residence time of semi-labile DOM (100 to 1000 days) obtained from ecosystem models (Luo et al, 2010). Interestingly, the carbohydrate content of HMW DOM has been observed to decrease with depth indicating that polysaccharides are a major bio-reactive component McCarthy et al, 1993).…”
Section: Introductionsupporting
confidence: 65%
“…Williams & Druffel (1987) found that open-ocean surface waters accumulate DOC enriched in radiocarbon (∆ 14 C of -146‰) relative to deep waters (∆ 14 C -540‰) reflective of the active cycling of newly fixed bomb radiocarbon but also indicative of the existence of a major old and refractory organic carbon reservoir that cycles through the ocean's conveyor over the course of thousands of years (Druffel, Williams, & Suzuki, 1989). In turn, the timescales associated with the turnover of semi-labile DOM -weeks, months or a few years -are derived from models that use labile and refractory DOM residence times as end members to constrain the turnover time of the remaining DOM inventory (Carlson & Ducklow, 1995;Davis & Benner, 2007; Druffel, Williams, Bauer, & Ertel, 1992;Luo, Friedrichs, Doney, Church, & Ducklow, 2010;Ogawa & Tanoue, 2003). These results warranted the need to chemically characterize DOM in detail to understand why it accumulated in the ocean and explain the predicted residence times of the different pools of DOM.…”
Section: The Biogeochemical Nature Of Dommentioning
confidence: 99%
“…These alternative sources may come from a wide variety of origins including carbon release through microbial loop and viral lysis, both based on BP itself. These carbon sources could be complementary to noncontemporary semi‐labile organic carbon, which has been suggested as supporting a large part of BCD in oceanic waters (Luo et al ., 2010). This ecological time scale is also relevant to the biological processes used in ecological models, where the concept of bacterial independence on phytoplanktonic production may be applied.…”
mentioning
confidence: 97%
“…They are also valuable for determining the magnitude and importance of processes that are difficult to measure and observe in the field. Many recent coastal and open ocean biogeochemical ecosystem models have included DOM (Anderson and Pondaven, 2003;Anderson et al, 2007;Anderson andWilliams, 1998, 1999;Aumont et al, 2003;Baklouti et al, 2006a,b;Druon et al, 2010;Faure et al, 2006;Grégoire and Soetaert, 2010;Llebot et al, 2010;Luo et al, 2010;Nakata and Doi, 2006;Pahlow and Vézina, 2003;Pahlow et al, 2008;Polimene et al, 2006Polimene et al, , 2007Ruardij et al, 2005;Salihoglu et al, 2008;Schmittner et al, 2005;Vichi et al, 2007) in order to better simulate and understand biogeochemical cycles. Carbon and nitrogen are typically accounted for in these models, although a few include phosphorus as well.…”
Section: Introductionmentioning
confidence: 99%